THE EFFECT OF SERVICE QUALITY AND CUSTOMER TRUST ON CUSTOMER SATISFACTION AND CUSTOMER LOYALTY PT SURYA RAFI BERSAUDARA - Untung Surapati; Suharno Suharno; Zainal Abidin (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2020)
This study aims to determine the effect of service quality and customer trust on customer satisfaction and customer loyalty of PT Surya Rafi Bersaudara. The population in this study were customers of PT Surya Rafi Bersaudara with a total of 75 respondents. The method of data collection is done by giving a list of questions or questionnaires to respondents who are customers at PT BKI , where the questionnaire is distributed to these customers. This study uses a data analysis tool that is partial Least Square (PLS), then this study uses the analysis method of structural equation models or Path Analysis to determine the causal relationship between latent variables contained in structural equations. The tool used in data processing using the Smart PLS program. The results of this study indicate that 1) service quality has a significant effect on customer satisfaction, 2) customer trust has a significant effect on customer satisfaction, 3) service quality has a significant effect on customer loyalty, 4) customer trust has no significant effect on customer loyalty, 5) customer satisfaction has a significant effect on customer loyalty. Keywords: Service Quality, Customer Trust, Customer Satisfaction, Customer Loyalty